Antonio Bonfini on Dalmatia, Croatia and Slavonia in the fifteenth century - Grgin, Borislav (Array, 2012)
The paper analyzed and tried to contextualize Bonfini’s image of medieval Dalmatia, Croatia and Slavonia. It focused on the fifteenth century. Bonfini was primarily interested in political history, with a particular emphasis on important individuals and glorious military deeds. Therefore, the main Croatian actors in his chronicle were Croatian and Slavonian warlords, bans and magnates. The main themes were the wars and battles against the Ottomans, the struggle with the Venetians for the Dalmatian coastal towns and islands and occasionally internal political turmoil in Slavonia or Croatia. The quantity of and importance given to the information regarding the three late medieval regna clearly demonstrate that they were only of marginal importance to the court circles of King Wladyslaw II and reflect the peripheral position the late medieval Croatian lands had from the viewpoint of the central authorities.